Active RFID : Real Time Location System (RTLS) - Ng, Bing Qiang. (2012)
In this project, a firmware was implemented for real time locating system (RTLS) using active RFID. The focus of this project was to improve on the firmware of the RTLS system. Both the positioning algorithms and RTLS application were not within the focus of this project.